TANTANGAN DAN SOLUSI PROBLEMATIKA PENDIDIKAN MULTIKULTURAL DI SEKOLAH DASAR - Chairunnisa, Putri; Azizah, Nur; Zulfikram, Riki; Shafa Saiddina, Cresna; Khairunnisa, Aura; Yatri, Ika; Azhar Nawawi, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Multicultural education is an educational approach aimed at instilling the values of tolerance, equality, and appreciation for cultural, religious, ethnic, and social diversity. In Indonesia’s pluralistic context, multicultural education in elementary schools plays a crucial role in shaping students' character from an early age so they can coexist harmoniously. This study aims to identify the challenges and propose solutions for implementing multicultural education at the elementary level. The research employed a literature review method by examining various sources, including books, academic journals, and educational policy documents. The findings reveal several major challenges: limited teacher understanding of multicultural principles, lack of religiously diverse teaching staff, homogeneous student backgrounds, and insufficient training and culturally responsive teaching materials. Additionally, the digital era introduces new challenges in terms of media literacy and digital ethics among students. Solutions proposed include curriculum revision, continuous teacher training, development of inclusive learning materials, community and parental involvement, and the use of digital media based on multicultural values. Multicultural education must be applied systematically and become an integral part of the school’s vision and culture. In conclusion, multicultural education is not only essential for creating inclusive learning environments but also serves as the foundation for building a democratic, civil, and culturally rooted generation capable of facing global challenges with resilience.